Professional Pressure And Impact On The Performance Level Of Teachers Of Physical And Sports Education In Algeria. - Ghidi, Abdelkader (sports creativity, 2025)
To work an important place in the individual's life because of its role and importance, it is not only a means of earning a livelihood but also a means of satisfying a lot of motivation and psychological needs, it is the focus of social activity in which the individual should achieve as much consensus as possible. The rapid development of the world today, and the world of occupation, has intensified efforts for change in various fields and areas, social, organizational, economic, and even political, which has made organizations and institutions suffer from a number of particular problems related to the human race by trying to appease him and relieve his suffering as a result of the pressures he gets professional in and out of work, understanding professional pressures in their manifestations and forms and identifying patterns of stressful situations, Its various sources help to explain the phenomena facing the Algerian school in particular. The first to use the term “stress” is” sely hans”. (bochra ismail.2008) The teaching profession plays a great role in the development of society and given the role of teacher and professor in this profession, there has been a growing interest in the teacher, and the consideration of his situation and the factors affecting its effectiveness has increased. The teacher and professor are a key pillar of the educational process, the success and failure of this process depends mainly on it, and the study confirms in the fields of education and mental health, psychological pressure (subjective and objective) is very important in influencing the lives of individuals and groups. Success in many works Depends on the degree of psychological and social harmony of the individual and the community, and that psychological stress and pressure prevent self-adaptation and the environment surrounding the ordinary man, how is it for the teacher. The teacher lives in political, economic and educational circumstances, causing tension and psychological stress, it makes the confiscation of subjective and objective available in life, at the level of the natural, social and educational environment in which educational work is practiced ,where she said “chandra batl” in 1991, the stress has many negative effects on humans, from dry mouth and head pain …etc. (bochra ismail.2008) where psychological pressure is one of the most important features of the present day, that is witnessing developments and rapid changes in all spheres of life, and psychological pressures are part of human life due to the many challenges they face in this age.